Developing global soil health metrics: Is SOM the key to grassland soil health? - Horrocks, Claire; Arango, Jacobo; Nunez, J.; Arévalo, Ashly; Cardoso Arango, Juan Andrés; Dungait, Jennifer (2018)
A healthy agricultural soil can maintain productivity, whilst delivering essential ecosystem services. An unhealthy soil can result in erosion, compaction and reductions in above and below ground diversity, nutrient cycling efficiency, drought tolerance and yield1. Grasslands for livestock production cover 26 % of total global ice free land 2, improvement of grassland soil health is essential for global food security. We aimed to combine a range of ‘low-tech’ and ‘hi-tech’ methods to understand the effect of different forage varieties and management techniques on soil health in both temperate (UK) and tropical (Colombia) grasslands and to develop a scientifically ratified soil health assessment protocol for use by farmers globally.